OFDM with Transmit and Receive Antenna Selection Based on Subcarrier Groups - Remlein, P.; Cogalan, T.; Gucluoglu, T. (IEEE, 2012)
In this paper, the performance of coded OFDM transmission over multiple antennas is explored when joint transmit and receive antenna selection is employed. The channel is assumed as Rayleigh frequency selective fading channel and only receiver is assumed to have perfect channel state information (CSI). The performance of MIMO OFDM system using pragmatic coding techniques such as convolutional coding (CC) and space-time block coding (STBC) with antenna selection based on subcarrier groups and other types such as all-tone, per-tone and hybrid techniques are obtained via computer simulations. The results suggests that joint antenna selection particularly based on subcarrier groups can be a desirable option in Worldwide Interoperability for Microwave Access (WiMAX) and Long Term Evolution (LTE) standards.
Keywords: PERFORMANCE; Computer Science; Engineering; Telecommunications